Reading Skill : Correlation Between Reading Speed and Reading Comprehension - Windi Windi; Nasriandi Nasriandi; Syahrir Syahrir (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This article aims to discover whether there is a relationship between students  reading speed and students' reading comprehension. The research approach is quantitative in nature, in which the authors use SPSS 22 to calculate students' reading speed and the number of correct answers they have answered. Research participants were 20 students of class XI IPA 2 Madrasah Alyah Negeri Palopo. The research instrument was nrtive text, where students read the text quickly and the researcher counted the time using a stopwatch, then students answered questions based on the text. As a result of the study, the authors found that there is a relationship between reading speed and students' reading comprehension where the Pearson correlation value showed 0.000 or lower than 0.05.